Tribological study of polyol ester-based biolubricants and the effect of molybdenum sulphide as lubricant additives / Nurul Adzlin Zainal - Nurul Adzlin, Zainal (2019)
The possible scarcity of oil and gas resources in the future (whether in quantity or areas of availability) is a major concern throughout the world. For this reason, governments all over the world are working on reducing their dependence on imported energy resources. Alternative energy resources such as bioethanol, biodiesel and biomass have gained prominence over the years in order to substitute petroleum-derived products. Biolubricants have also gained importance as alternatives to conventional petroleum-based lubricants in various applications, especially in the automotive industry. Biolubricants (also known as bio-based lubricants) are appealing alternatives for mineral-based lubricants because of their biodegradability and good lubricity. Owing to the advantages of biolubricants, the study was conducted to investigate the physicochemical properties and wear preventive characteristics of polyol ester-based biolubricants, namely, neopentyl glycol (NPG), trimethylolpropane (TMP), and pentaerythritol (PE) ester-based biolubricants. In addition, different concentrations of surface-capped molybdenum sulphide (known as friction modifier additive) were blended into the polyol ester-based biolubricants to study the effect of additive on the friction and wear properties. A four-ball wear tester is used to investigate the tribological properties (coefficient of friction and wear scar diameter) of the biolubricants in accordance with ASTM standard test methods, and the results are compared with those for paraffin oil and commercial lubricant. In general, the tribological performance of biolubricants is comparable to that for paraffin oil, and therefore, these polyol ester-based biolubricants are potential alternatives to replace mineral-based lubricants. Besides that, the addition of molybdenum sulphide improves the friction and wear properties of the polyol ester-based biolubricants.